How certain are El Niño–Southern Oscillation frequency changes in Coupled Model Intercomparison Project Phase 6 models?. (20th November 2022) - Fix, Fiona; Buehler, Stefan A.; Lunkeit, Frank
Abstract: El Niño–Southern Oscillation (ENSO) is one of the most important modes of climate variability on interannual timescales. We aim to find out whether a change in ENSO frequency can be predicted for the nearer future. We analyse the unforced pre‐industrial control run and the forced 1%/year CO2 increase run for an ensemble of 43 general circulation models that participated in the Coupled Model Intercomparison Project Phase 6 (CMIP6). We assume that the uncertainty of ENSO frequency trend estimates from an ensemble is caused by apparent trends as well as model differences. The part of the uncertainty caused by apparent trends is estimated from the pre‐industrial control simulations. As a measure for ENSO frequency, we use the number of El Niño‐ and La Niña‐like months in a moving 30‐year time window. Its linear decadal trend is calculated for every member. The multimember mean of the trend for both experiments is less than 0.7 events per decade. Given that the standard error is of the same order of magnitude, we consider this a negligible trend. The uncertainties are large in both experiments and we can attribute most of the intermember variability to apparent trends due to natural variability rather than different model reactions to CO2 forcing. This means that the impact of intermodel differences might have been overstated in previous studies. Apparent trends make it very difficult to make reliable predictions of changes in ENSO frequency based on 120‐year time series. Abstract : The 1pctCO2 and piControl ensembles from CMIP6 are analysed for 43 models with a focus on changes in ENSO frequency. We find that most of the intermember variability can be attributed to natural variability instead of model differences. Therefore, the uncertainty can only marginally be reduced and it is very difficult to reliably predict changes in ENSO frequency on a timescale of 150 years.